Analysis Of The Agricultural Sector’s Contribution To The Increase Of GRDP In The Regency Of Grobogan - Syaroni, Muhammad; Setiyani, Rahmawati; Sepfrian, Bimoseno (LPPM Universitas Duta Bangsa Surakarta, 2024)
Grobogan Regency is one of the regencies with the largest agricultural area in Central Java Province, with 134,174.10 hectares in 2023. In the same year, the growth rate of Gross Regional Domestic Product in the agricultural sector in Grobogan Regency was only 0.17%. This research uses Location Quotient Analysis, Shift Share Analysis, and Descriptive Analysis methods. The data used is secondary data in the form of Gross Regional Domestic Product (GRDP) at market prices by sectors in Central Java Province and Grobogan Regency from 2019 to 2023. The objectives of this study were to (1) analyze the growth and competitiveness of the agricultural sector, (2) analyze the ability of the agricultural sector to increase the GRDP of Grobogan Regency. As a result, from 2019 to 2023, the agricultural sector in Grobogan Regency has contributed 25.77%; 26.78%; 26.76%; 25.82%; and 24.63% respectively to the economy of Grobogan Regency. The value of KPN in the agricultural sector of Grobogan Regency is 0.11. In the Proportional Growth Component, the agricultural sector in Grobogan scored -0.05. The Regional Growth Share component of the sector was also negative, -0.02. The Shift Share value of the agriculture sector was 0.05% from 2019 to 2023. The agricultural sector in Grobogan Regency is experiencing slowing growth and is not competitive despite being a basic sector. High food crop production in Grobogan Regency is expected to increase the role of the agricultural sector in the Gross Regional Domestic Product of Grobogan Regency.